Regenerative-Based Green Supply Chain Management Model for the Construction Industry - Oyefusi, ON; Enegbuma, WI; Brown, A; Zari, MP (IOP Publishing, 2022)
Green Supply Chain Management (GSCM) is considered to be the most effective management tool that aims to integrate environmental sustainability thinking into the built environment. This is in relation to its ability to substantially reduce greenhouse emissions, energy consumption, pollution, and other drivers of negative environmental change in the built environment. Despite the implementation of GSCM practices, climate change continues to occur with a steady rise in greenhouse gas emissions per year that are associated with the built environment. Hence, there is a need for a proactive regenerative approach that focuses not only on reducing negative environmental footprints but also aims to create net positive impacts on the environment. This study aims to address this issue by first identifying the dominant forms of construction GSCM practices and their performance limitations through a Systematic Literature Review (SLR). The result revealed that regenerative factors were lacking in current GSCM practices. To further explore the nature of expanding current GSCM practices, a regenerative-based GSCM model was developed that demonstrates the relationship between regenerative and GSCM practices. This research addresses the gaps in current GSCM practices which could serve as a strategic response to climate change in terms of both mitigation and adaptation responses.
Keywords: 41 Environmental Sciences; 4104 Environmental Management; 13 Climate Action; 12 Responsible Consumption and Production; 30 Agricultural, veterinary and food sciences; 37 Earth sciences; 41 Environmental sciences